Empedocles and the Other Physiologists in Aristotle’s Physics II 8 - Giardina, Giovanna R. (Peitho. Examina Antiqua, 2016)
In this paper I propose to show: 1) that in Phys. II 8 Aristotle takes Empedocles as a paradigm for a theoretical position common to all philosophers who preceded him: the view that materialism implies a mechanistic explanation of natural becoming; and 2) that, since Empedocles is regarded as a philosopher who clearly expresses the position of all mechanistic materialists, Aristotle builds his teleological arguments precisely to refute him. Indeed, Aristotle believes that refuting the arguments of Empedocles – the champion of mechanism – means refuting the mechanistic theory itself. In order to illustrate this point, I will discuss some passages from Phys. II 8, while also turning to consider the Neoplatonic commentators on Aristotle’s Physics. I will then endeavour to explain why in 198b19 ff. Aristotle formulates the argument of rain, which has attracted so much attention from scholars of the Physics: I will consider whether Aristotle believes that rain serves a purpose, contrary to what he claims with regard to meteorological phenomena in Meteorologica.